Issues regarding the design intervention and conservation of heritage areas: the historical pedestrian streets of Kuala Lumpur - Bindajam, Ahmed; Mohmad Hussin, Muhamad Fadrul Hisham; Al-Ansi, Nashwan; Mallick, Javed (MDPI, 2020)
This study focused on the areas of Petaling Street and Jalan Hang Kasturi, Kuala Lumpur, in a historical enclave that is well known locally for its cultural, architectural, and historical interest that is worth preserving and conserving. To fulfill the purpose of enhancing the areas, the local authority introduced a covered pedestrian street, which is said to be more convenient for shoppers, considering the tropical climate of Kuala Lumpur. This effort is believed to have been done without any consultation with heritage conservators and activists, thus invoking a debate regarding its many pros and cons. This study examined the arguments concerning the intervention in the heritage area from various groups of stakeholders that are directly involved. Furthermore, this paper presents the method of implementation used by the local authority when executing a conservation project. The collection of primary and secondary data in the form of surveys and interviews with the professionals, traders, and officials in the local area was carried out. The findings show that the majority of the respondents had no objection to the modern intervention in the Heritage Enclave, including the roofing structure, except for its design. This study also found that the intervention did not affect the heritage value of the place, but at the same time, brought concerns regarding the extemporaneous method taken by the local authority when implementing the project.